AKTIVITAS ANTIOKSIDAN DAN ANTI HIPERKOLESTEROLEMIA EKSTRAK UMBI BAWANG DAYAK (Eleutherine bulbosa [Mill.] Urb) - Yani Andryani; Anna Maria Dewajanti; Adelina Simamora (Atma Jaya Catholic University of Indonesia, 2022)
Introduction: High cholesterol levels can build up plaque inside the lining of the artery wall leading to coronary heart disease. Dayak onion bulbs (Eleutherine bulbosa (Mill.) Urb) contain flavonoids that can act as antioxidants and are believed to reduce blood cholesterol level. This study investigated the flavonoid content and antioxidant activity of Dayak onion tuber extract, and their effect on total blood cholesterol levels. Methods: Dayak onion bulbs were extracted by maceration (ethanol 70%). Total flavonoid was determined by a colorimetric method using AlCl3. Antioxidant activity was determined based on DPPH radical scavenging activity. Anti-hypercholesterolemia effect was studied in vitro. Thirty-six white male rats (Rattus novergicus) were divided into 6 groups: healthy rats, hyper-cholesterol rats, hyper-cholesterol rats treated with simvastatin (18 mg/bw) and rutin (75 mg/bw) as positive controls, hyper-cholesterol rats treated with dayak union bulbs extracts (75 and 150 mg/bw). Measurement of total cholesterol levels was performed using CHOD-PAP method. Data were analyzed using paired t-test and one-way anova. Results: Flavonoids were present in onion bulb extract with a concentration of 1.7 mg/g dried biomass. The antioxidant activity of the extract (IC50 0.37 mg/mL) was weaker than that of rutin (IC50 15.58 µg/mL). The addition of dayak onion bulbs extract dose of 150 mg/kg bw was the best dose in reducing total blood cholesterol levels on the 14th day, p = 0,001. Conclusion: dayak onion bulbs can be further investigated for application as anti hypercholesterolemia agent.